Relationship Between a Systemic Inflammatory Marker, Plaque Inflammation, and Plaque Characteristics Determined by Intravascular Optical Coherence Tomography - Raffel, O. Christopher (2007)
OBJECTIVE: The purpose of this study was to evaluate the relationships between the peripheral white blood cell (WBC) count, local plaque fibrous cap macrophage density, and the morphological features and presence of thin-cap fibroatheromas (TCFA) identified by optical coherence tomography (OCT). METHODS AND RESULTS: OCT was performed in patients undergoing catheterization. Images were analyzed using validated criteria for plaque characteristics. Baseline WBC count correlated with macrophage density (r=0.483, P<0.001). Both parameters were associated with lipid-rich plaque and correlated inversely with plaque fibrous cap thickness (r=−0.547 for macrophage density and −0.423 for WBC count, P<0.015). Plaques classified as TCFA had a higher median macrophage density than non-TCFA plaques (7.4 versus 4.99, P<0.001). Patients with TCFA had a higher WBC count compared with those without TCFA (11.0 versus 7.9, P=0.007). Receiver operator curves for WBC count, macrophage density, and these combined parameters for prediction of TCFA showed the area under the curves were 0.88, 0.91, and 0.97 (P<0.001), respectively. CONCLUSION: This study provides the first in vivo data linking the peripheral WBC count, plaque fibrous cap macrophage density, and the characteristics and presence of TCFA. Macrophage density correlated with the WBC count, and both parameters independently and particularly in combination predict the presence of TCFA.